Investigation of the processes of excitation of bound states of a hydrogen atom - Nuraly, А.T.; Seisembayeva, M.M. (Recent Contributions to Physics, 2024)
One of the most important areas of plasma physics is the physics of elementary processes, that is, the physics of processes occurring during collisions of molecules, atoms, ions, electrons and photons. The composition of plasma, its thermodynamic, transport, optical and other properties are determined by the processes occurring in the plasma system, as well as their speeds. For this reason, by analyzing collision processes, it is possible to investigate certain properties of the plasma. Traditionally, the study of elementary processes within a specific model begins with the study of the scattering cross section, when the first estimates are made using simple methods. These methods include the Born method, which can and should be applied in practice. In this work, studies were carried out of the influence of collective effects in plasma on the states and energies of hydrogen atoms and hydrogen-like ions, as well as on excitation processes. Quantum mechanics methods were used in the research process, including the variational method and the perturbation theory, especially the Born approximation for inelastic scattering processes. As a result of the work, data were obtained based on the Born approximation for the process of excitation of a hydrogen atom by electron impact. The Born approximation shows better results in the case of high-energy collisions. The results obtained during the study have scientific and experimental significance, since they make it possible to determine the velocity coefficients through the calculation of scattering cross sections. These coefficients, in turn, are necessary to solve the kinetic equation used to describe the sedimentation (concentration) of particles in the plasma.